PENGELOLAAN TEMBAWANG SUKU DAYAK IBAN DI DESA SUNGAI MAWANG, PURING KENCANA, KAPUAS HULU, KALIMANTAN BARAT - Yasri Syarifatul Aini; Nyoto Santoso; Rinekso Soekmadi (Department of Forest Resources Conservation and Ecotourism - IPB University, 2016)
Dayak Iban Ethnic cannot be separated of interaction with the forest (tembawang) as a place to fulfill of variety needs such as food source, building material, traditional medicine, traditional ceremonies, craft and so on. It is important to know all aspect about tembawang and existence. The data were collected by in depth interviews to the village officials, officials and indigenous community representative, analyze with descriptive qualitative and SWOT. Sungai Mawang Village has 15 tembawang, spacious 12.52 ha and 147 types of plants with complete stratification such as natural forests. Tembawang management is governed by customary law. Access unlimited use but require a permit customs officials. Tembawang has the function and value is very important because it is part of the tradition, culture and customs of the people, economic needs and conservation. The Dayak Iban manage tembawang in good condition, with the result that maximizing managemen and potential for achieve maximum progress. Sustainability of tembawang management needs the support of the government as the policy holder and indigenous peoples itself, besides strengthening traditional values/culture in various aspects. Keywords: Dayak Iban ethnic, management, sustainability, SWOT, tembawang